P3.409* Sexual health in the Adult Film Industry (AFI): Environmental Barriers and Facilitators of Sexually Transmitted Infection (STI) Transmission. (13th July 2013) - Lilleston, P.; Mead, E.; Cernigliaro, D.; Sherman, S. G.
Abstract : Background: Adult film is a legal form of sex work in the U.S. that places performers at heightened risk of acquiring an STI. However, very little public health research exists on the environmental factors that influence STI transmission in the AFI. Methods: We explored the nature of the AFI's STI risk environment in semi-structured in-depth interviews (N = 28) with performers, producers, directors and key informants from December 2012 through February 2013. Recruitment was conducted via purposive and snowball sampling. Interviews took place in-person and via phone. Data were analysed using an inductive approach in Atlas-ti . Results: Participants described facilitators and barriers to STI transmission at the policy, economic, and social levels. On the policy level, mandatory STI testing and exclusion from work based on a positive test were perceived as largely effective in preventing STIs. However, some participants believed the required panel missed prevalent STIs (e.g. herpes) and modes of transmission (e.g. oral, anal). Unless required by the production company, condom use was rare, and no formal mechanisms existed for notifying partners of an STI. On the economic level, performers' earnings increased with number of sexual partners and riskier sexual acts. Most performers had no health insurance, paying out-of-pocket for STI testing and treatment. Due to the AFI's unsteady payment structure, many performers engaged in sexual escorting to supplement income. On the social level, seasoned performers felt empowered to advocate for their preferences regarding sexual practises and partners on set. However, fear of losing work, compounded by competition among performers, could put newer performers at greater risk for an STI. Although most performers preferred not to use condoms on set, participants described implicit and explicit pressure from producers and directors towards non-condom use. Conclusion: This study highlights important characteristics of the AFI environment that could be targeted for STI prevention interventions.